2006
DOI: 10.1016/j.clpt.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coagulation factor, vitamin K epoxide reductase complex subunit 1, and cytochrome P450 2C9 gene polymorphisms on warfarin dose requirements

Abstract: Polymorphisms in warfarin drug target and metabolizing enzyme genes, in addition to nongenetic factors, were important determinants of warfarin dose requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(226 citation statements)
references
References 43 publications
11
214
1
Order By: Relevance
“…The ultimate goal was to improve our understanding of the worldwide allele frequency distribution of these polymorphisms and to discuss the results in light of the known effect of these markers on warfarin dosing and the differences in average warfarin dosing that have been reported The VKORC1 gene is believed to be the most important individual predictor of warfarin dose. 29,38 Previous research has shown that the derived T allele of the rs9923231 polymorphism, which is located in the promoter region of the gene, is associated with lower warfarin dose requirements. Moreover, there is evidence indicating that the rs9923231 T allele is associated with a reduction of VKORC1 mRNA levels of up to 70%, in comparison to the wild-type allele.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal was to improve our understanding of the worldwide allele frequency distribution of these polymorphisms and to discuss the results in light of the known effect of these markers on warfarin dosing and the differences in average warfarin dosing that have been reported The VKORC1 gene is believed to be the most important individual predictor of warfarin dose. 29,38 Previous research has shown that the derived T allele of the rs9923231 polymorphism, which is located in the promoter region of the gene, is associated with lower warfarin dose requirements. Moreover, there is evidence indicating that the rs9923231 T allele is associated with a reduction of VKORC1 mRNA levels of up to 70%, in comparison to the wild-type allele.…”
Section: Discussionmentioning
confidence: 99%
“…Dose variance explained by VKORC1 and CYP2C9 was 25% and 9%, respectively, confirming and refining previous estimates. 10,19 Genotype imputation using data from the European HapMap (CEPH European) SNPs and additional variants from approximately 1000 selected candidate genes 26,27 expanded our tests of association in the index population to more than 3 million SNPs across the human genome. However, no significant SNPs outside of those previously described gave robust signals for association.…”
Section: Replication Resultsmentioning
confidence: 99%
“…This patient set has previously been studied for the effects of VKORC1 and other candidate genes on stabilized warfarin dosing. 19 Stable warfarin dose was defined by less than 10% variability between clinic visits and an INR within the target range at more than 3 visits. Exclusion criteria for these patients were liver cirrhosis, advanced malignancy, hospitalization within 4 weeks before the index visit, or febrile/diarrheal illness within 2 weeks of the index visit.…”
Section: Study Setting and Designmentioning
confidence: 99%
See 2 more Smart Citations